A revision of the genus Bromeloecia Spuler (Diptera: Sphaeroceridae: Limosininae) - Yau, Tiffany; Marshall, Stephen A. (Zootaxa, 2018)
The genus Bromeloecia Spuler is revised, including 20 new and one previously described species. A key to species is provided, and species-level phylogenetic relationships are assessed on the basis of morphological characters. The B. winnemana species group, a mainly Nearctic species group characterized by ornamental processes on the hind tarsus, is excluded from the revision but is diagnosed, included in the key and considered within the phylogeny of Bromeloecia as an operational taxonomic unit. B. bromeliarum (Knab and Malloch) is redescribed and the following new species are described: B. abundantia, B. aculatus, B. aurita, B. balaena, B. brachium, B. cercarcuata, B. coniclunis, B. diabolunguia, B. ephippium, B. fractacincta, B. magna, B. peloris, B. pinna, B. ponsa, B. ramus, B. robustora, B. spathicercus, B. triunguia, B. undulata, and B. wolverinei.